Transformation of traditional Bugis architecture: a case study of Saoraja Seng in Soppeng Regency, Indonesia - Abidah, Andi; Jayadi, Karta; Dwiasta, Andi Yusdy (2025)
This study investigates the transformation of traditional Bugis architecture, focusing on Saoraja Seng in Soppeng Regency as a case study. Saoraja Seng exemplifies the evolution of Bugis architectural practices in response to colonial influences and modern needs. This research examines the adaptation of traditional design elements, including the hip roof, the use of Malay-style windows, and symbolic ornaments such as pucuk rebung and lawasoji quadrilaterals. Through an analysis of architectural changes and their cultural implications, the study reveals how Saoraja Seng integrates traditional Bugis aesthetics with colonial architectural influences while preserving cultural and symbolic values. The study employs theoretical frameworks from Claude Lévi-Strauss's structuralism and Paul Oliver's vernacular architecture principles to understand how these adaptations reflect shifts in social and cultural contexts. The findings highlight the dynamic nature of architectural traditions and the ongoing negotiation between heritage and modernity in Bugis architecture.